Speech Events and Social Dynamics in the Video “Mama Lela Ngamuk Parah” on the YouTube Channel Dika_bj - Anggraini, Desinta; Hafizah, Alizatul; Atmawijaya, Aflah Gian; Rumilah, Siti (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the speech events in the Mama Lela drama, specifically the episode titled “Mama Lela Ngamuk Parah,” along with its communicative framework. The aim is to understand how elements of communication such as setting, participants, purpose, and conversational sequence shape meaning in the dialogue between characters. In addition, the study explores the influence of speech partners in shaping the flow of conversation and the social dynamics among the characters.The method used is descriptive qualitative, employing discourse analysis that considers cultural and social contexts. The findings indicate that the elements of communication in Hymes’ model play a significant role in shaping the structure and meaning of verbal interaction. Furthermore, the study reveals how power relations, emotions, and social values are reflected through the characters’ speech.Thus, this research not only explains the communication patterns in Mama Lela, but also provides insight into how language is used to express conflict, social relationships, and cultural identity within a dramatic work.